Abnormal circadian rhythm in patients with GRIN1-related developmental epileptic encephalopathy. (July 2019) - Scala, Marcello; Amadori, Elisabetta; Fusco, Lucia; Marchese, Francesca; Capra, Valeria; Minetti, Carlo; Vari, Maria Stella; Striano, Pasquale
Abstract: GRIN1 encodes the obligate subunit (GluN1) of glutamate N-methyl-d -aspartate receptor (NMDAr). Pathogenic variants in GRIN1 are a well-known cause of infantile encephalopathy characterized by profound developmental delay (DD), variable epileptic phenotypes, and distinctive behavioral abnormalities. Recently, GRIN1 has also been implicated in the pathogenesis of polymicrogyria (PMG). We investigated two patients presenting with severe intellectual disability (ID), epilepsy, stereotyped movements, and abnormal ocular movements. They showed distinctive circadian rhythm alterations and sleep-wake patterns anomalies characterized by recurrent cyclic crying or laughing spells. Genetic analysis led to the identification of two distinct de novo variants in GRIN1 affecting the same amino acid residue of an important functional protein domain. Recent advances in circadian rhythm and sleep regulation suggest that abnormal GluN1 function might play a relevant pathogenetic role for the peculiar behavioral abnormalities observed in GRIN1 patients. Our cases highlight the relevance of circadian rhythm abnormalities in epileptic children as a clue toward GRIN1 encephalopathy and expand the complex phenotypic spectrum of this severe genetic disorder. Highlights: GRIN1 encodes the obligate subunit of glutamate N-methyl-d -aspartate receptor (NMDAr). GRIN1 deficiency causes a severe early-onset epileptic encephalopathy. This study describes distinctive circadian rhythm alterations in GRIN1 patients. Sleep-wake anomalies and cyclic crying or laughing spells might foster early diagnosis. Manipulating glutamate metabolism might be a therapeutic approach in GRIN1 patients.